Search
Ask a question
0

Simplify the given expression

3[2+6(4-3)]
 

2 Answers by Expert Tutors

Tutors, sign in to answer this question.
Vivian L. | Microsoft Word/Excel/Outlook, essay composition, math; I LOVE TO TEACHMicrosoft Word/Excel/Outlook, essay comp...
3.0 3.0 (1 lesson ratings) (1)
0
Hi Darian;
We will distribute within the parentheses, first.  The brackets are second.
3[2+6(4-3)]
6(4-3)
(6)(4)=24
(6)(-3)=-18
24-18
3(2+24-18)
(3)(2)=6
(3)(24)=72
(3)(-18)=-54
6+72-54
78-54
24
William S. | Experienced scientist, mathematician and instructor - WilliamExperienced scientist, mathematician and...
4.4 4.4 (10 lesson ratings) (10)
0
3[2 + 6(4 - 3)] = 3[2 + 6(1)] = 3(8) = 24